Antiretroviral dose optimization: the future of efavirenz 400 mg dosing. Issue 4 (July 2017) - Boffito, Marta; Lamorde, Mohammed; Watkins, Melynda; Pozniak, Anton
Abstract : Purpose of review: Antiretroviral (ARV) therapy costs in low-income and middle-income countries are major concerns, and lower doses of first-line treatment components, when possible, would save millions of dollars, which could be used to treat more people living with HIV. Recent findings: The Encore-1 study, followed by a detailed pharmacokinetic analysis of efavirenz 400 versus 600 mg once daily, produced enough information for the most recent ARV treatment WHO guidelines to include efavirenz 400 mg among agents used for first-line treatment. However, data on efavirenz 400 mg plasma concentrations during pregnancy and when coadministered with rifampicin-containing antituberculosis (TB) treatment are not yet available as formal pharmacokinetic studies under these circumstances are ongoing. Summary: Although efavirenz at a daily dose of 400 mg once daily in combination with tenofovir disoproxil fumarate and emtricitabine has shown noninferiority to the approved 600 mg once-daily dose, large global uptake has been delayed by the lack of data on drug exposure during pregnancy and anti-TB treatment. Knowledge on efavirenz 400 mg exposure in these scenarios will arise in mid-late 2017.